Problem Based Learning Penerapan Model Problem Based Learning (PBL) Berbantuan PPT Interaktif Untuk Meningkatkan Hasil Belajar Berbasis HOTS Tema Cuaca Pada Siswa Kelas III di UPTD SATDIK SDN Tanjungrejo 03 Kabupaten Jember - Ayu Dewi Wahyuni; Agustiningsih; Arik Aguk Wardoyo (Universitas Negeri Surabaya, 2023)
Based on the results of interviews, it shows that student learning outcomes are still low in the less category. This is due to the use of models and media that are less varied and innovative. One model that can be used to improve HOTS-based student learning outcomes is the PBL model with the help of Interactive PPT. This type of research is Classroom Action Research (CAR). The subjects used were class III students, totaling 26 students. Data collection techniques include interviews, tests and documentation. Based on the results of the analysis, student learning outcomes in the classical pre-cycle were 58%, increasing to 72% in cycle I and increasing again to 83% in cycle II. Based on this description, it can be concluded that the application of the Problem Based Learning model assisted by Interactive PPT can improve HOTS-based learning outcomes with the weather theme sub-theme learning weather conditions 1 in class III students at SDN Tanjungrejo 03 Jember Regency.